Chemical Productions and Immunological Assessments of Cancer Vaccines According to Α-Galactosylceramide and Ganglioside Antigen - Noor Abd Al-Zahra Ali; Aysar Ahmed Ali; Khawla Abdulkader Ossama (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
iNKT cells, sometimes known as the immune system's "Swiss Army knife," have become key components of cancer vaccination treatments. Glycolipids that activate iNKT cells, including α-galactosylceramide (αGalCer), have been used to create self-adjuvanting anti-tumor vaccinations and can boost the immune response to co-delivered cancer antigens. The chemicals synthesis of ganglioside antigens, specifically (Neu5Gc) GM3 and GM3 antigen, and conjugations to αGalCer, and packaging into liposome as effective platforms for their in vivo deliverying are the main topics of this work. In mouse and human cell experiments, liposome containing, (Neu5Gc) GM3-αGalCer, GM3-αGalCer, and equimolar quantities of conjugates have thoroughly described and their capacities to activate iNKT cell has verified ex vivo. All subclasses of IgG antibodies were produced as a result of the candidates' potential to generate both TH1 and TH2 cytokines, according to in vivo immunization tests. Interestingly, this study shows serum antibody produced against the TACA were cross-reactive, both when they were produced separately and together. If tumor-selective antigens is selected, the ensuing antibodies response can be wider than expected, which has implications for future vaccine formulations.